Dissolved iron release by sediment and dust particles in Antarctic seawater greater than glacial flour and sea-ice particles - Corkill, Matthew; Meiners, Klaus Martin; Wongpan, Pat; van der Merwe, Pier; Creac'h, Layla; Feig, Sandrin; Nelson, Talitha; Smith, Abigail Jessica Rose; Townsend, Ashley T.; Twiname, Samantha; Lannuzel, Delphine (Marine chemistry, 2025)
Primary productivity by phytoplankton in the Southern Ocean can be limited by low iron concentrations. Iron limitation in the surface ocean around Antarctica may be alleviated by particle dissolution of dust from exposed rock, glacial flour, resuspended marine sediment, and sea ice. Ligands, which are ubiquitous in seawater, chelate some metals and keep them in solution. Ligands are thereby thought to increase metal solubility, including iron. Leaching studies of Antarctic particles from various sources are rare but important due to observed and predicted changes occurring around Antarctica, e.g., changes in sea ice and ice-free areas on the continent. Here, we quantified the solubility of iron in different particle types using vertical flow-through leaching experiments that simulated sinking through the water column and ran for 78 min of flow at 4 °C under trace metal-clean conditions. Both unaltered and ultraviolet-irradiated seawater leaching solution treatments were used to test the effect of organic ligands on iron dissolution, which was found to be non-significant. Sediment and dust released the most dissolved iron to seawater, followed by glacial flour, and then sea-ice particles (9.00 ± 9.92 × 10−2 and 3.18 ± 3.79 × 10−2, 1.97 ± 1.79 × 10−4, 1.37 ± 0.90 × 10−9 g DFe/100 g material, respectively). We discuss these laboratory results in relation to particle availability and how this may affect the supply of dissolved iron to Antarctic surface waters.
Online verfügbar 21 February 2025, Version des Artikels 28 February 2025
Gesehen am 23.07.2025